Coordination Template Reactions, Part III : complexes of Tetradentate 1,3,7,9 and 1,3,8,10 Tetraenes with Cu(II) & Ni(II) - Shukla, (Mrs.) P.R.; Rashmi, (Miss) R.; Sadhna Srivastava, (Miss); Ahmad, Nihal; Sharma, M.C.; Narain, Gopal (Asian Journal of Chemistry, 2010)
Eight macrocyclic complexes have been prepared using the template condensation reactions between glyoxal, ethylenediamine and propylenediamine. The complexes which possess the general formula M(L´ or L")X2 where M ═ Cu(II) and Ni(II); X ═ Cl–, SCN– and L´ or L" ═ macrocyclic ligand, have been assigned octahedral structures on the basis of analytical, magnetic and spectral measurements.